2005
DOI: 10.1161/01.res.0000183733.53101.11
|View full text |Cite|
|
Sign up to set email alerts
|

Cardiac Stem Cells Possess Growth Factor-Receptor Systems That After Activation Regenerate the Infarcted Myocardium, Improving Ventricular Function and Long-Term Survival

Abstract: Abstract-Cardiac stem cells and early committed cells (CSCs-ECCs) express c-Met and insulin-like growth factor-1 (IGF-1) receptors and synthesize and secrete the corresponding ligands, hepatocyte growth factor (HGF) and IGF-1. HGF mobilizes CSCs-ECCs and IGF-1 promotes their survival and proliferation. Therefore, HGF and IGF-1 were injected in the hearts of infarcted mice to favor, respectively, the translocation of CSCs-ECCs from the surrounding myocardium to the dead tissue and the viability and growth of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
383
1
6

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 474 publications
(409 citation statements)
references
References 31 publications
19
383
1
6
Order By: Relevance
“…These cells were capable of migrating into the infarcted area from surrounding nonischemic myocardium. This process involves the SCF/c-kit and HGF/c-met pathways (Linke et al, 2005;Urbanek et al, 2005) discussed below. Bearzi et al (2007) recently reported that human c-kit þ CSCs isolated from small samples of myocardium were able to expand, and differentiate into cardiomyocytes, endothelial and smooth muscle cells in vitro.…”
Section: C-kit 1 Cscsmentioning
confidence: 99%
See 2 more Smart Citations
“…These cells were capable of migrating into the infarcted area from surrounding nonischemic myocardium. This process involves the SCF/c-kit and HGF/c-met pathways (Linke et al, 2005;Urbanek et al, 2005) discussed below. Bearzi et al (2007) recently reported that human c-kit þ CSCs isolated from small samples of myocardium were able to expand, and differentiate into cardiomyocytes, endothelial and smooth muscle cells in vitro.…”
Section: C-kit 1 Cscsmentioning
confidence: 99%
“…Expression of c-met is directly regulated by HIF-1a under hypoxic conditions (Ceradini et al, 2004). Recent studies have demonstrated that HGF promotes proliferation and migration of resident c-kit þ CSC within the myocardium after MI (Linke et al, 2005;Urbanek et al, 2005). Those c-kit þ CSCs that expressed functional c-met were strongly attracted by a HGF gradient in vitro.…”
Section: Hepatocyte Growth Factor/c-metmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 It is cardioprotective and neuroprotective and contributes to tissue regeneration in other organs as well, partially due to anti-apoptotic, pro-angiogenic and mitogenic activities. 2,[10][11][12] Moreover, HGF attracts stem and progenitor cells, including cardiac stem cells, 13 neuronal stem cells, 14 endothelial progenitor cells 15 and mesenchymal stem cells (MSC), 4,9 which probably contributes to its tissue protective and regenerative effects.…”
mentioning
confidence: 99%
“…Recently, cardiac progenitors defined by coexpression of ckit, MDR1 and sca-1 were isolated from human hearts, 55 and in animal models of MI they were shown to be mobilized from the atria to the infarct zone after a gradient of hepatocyte growth factor and insulin-like growth factor 1 had been applied to the heart. 56,57 Another group of resident cardiac progenitor cells is characterized by the expression of the antigen 'islet 1' (isl1), and these isl1+ cells develop into cells with a mature cardiac phenotype including intact Ca 2+ -cycling and the generation of action potentials. 58 As mentioned earlier, SP cells can be isolated from the heart, and thus constitute a fifth cardiac progenitor phenotype that can acquire an adult cardiomyocyte phenotype when placed in a permissive environment.…”
Section: Resident Cardiac Progenitor Cellsmentioning
confidence: 99%